2021
DOI: 10.1186/s40168-021-01167-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation of the indoor mycobiome in daycare centers

Abstract: Background Children spend considerable time in daycare centers in parts of the world and are exposed to the indoor micro- and mycobiomes of these facilities. The level of exposure to microorganisms varies within and between buildings, depending on occupancy, climate, and season. In order to evaluate indoor air quality, and the effect of usage and seasonality, we investigated the spatiotemporal variation in the indoor mycobiomes of two daycare centers. We collected dust samples from different ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
3
14
1
Order By: Relevance
“…Thus, understanding the indoor fungal diversity could further our understanding of age-specific exposure pathways and transmission. For example, a recent study showed that less-occupied rooms in childcare centers were significantly different from the main rooms in fungal diversity, [ 21 ]. These findings, in addition to our own, have implications for understanding age-specific exposure to microbes and fungi and their different health outcomes [ 64 ], and highlights why studies on the microbiome of the built environment occupied by different age groups are important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, understanding the indoor fungal diversity could further our understanding of age-specific exposure pathways and transmission. For example, a recent study showed that less-occupied rooms in childcare centers were significantly different from the main rooms in fungal diversity, [ 21 ]. These findings, in addition to our own, have implications for understanding age-specific exposure to microbes and fungi and their different health outcomes [ 64 ], and highlights why studies on the microbiome of the built environment occupied by different age groups are important.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of fungi in the indoor environment include building materials, ventilation systems, human transmission (i.e. through fungi tracked into the building from environmental sources), and the greater outdoor environment [ 21 , 23 ], with indoor fungal communities in childcare centers dominated by the genera Aspergillus, Cladosporium, Penicillium, Alternaria, Rhizopus and Curvularia. High abundances of these fungi in built environments have been associated with various respiratory disorders such as asthma and allergic rhinitis [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study investigating indoor fungi in a housing facility in California, Adams et al showed that the outdoor air and not the residents structured the indoor mycobiome ( 12 ). Interestingly, in our recent study on the seasonality of the indoor mycobiome, the indoor environment was more influenced by the outdoor fungal diversity during summer and fall ( 10 ). Thus, as the community scientists in the present study performed sampling during early spring, we may have detected a stronger influence of indoor variables than, e.g., Shin et al ( 30 ), where samples were collected from August to October in a comparable climate in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, it was previously shown that the concentration of fungi in daycare centers is higher than that in homes ( 9 ). In several studies, the outdoor environment has been reported to be the main source of indoor fungi ( 10 13 ) due to the influx of spores through windows, entrances, and the ventilation system. Hence, the vegetation and climate that structure the outdoor fungi will indirectly also structure the indoor mycobiome ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation